Cytochrome P450 and ischemic heart disease: current concepts and future directions. (February 2014) - Rowland, Andrew; Mangoni, Arduino A
<x xml:space="preserve">Abstract</x> Introduction: The P450 enzymes (P450s) mediate the biotransformation of several drugs, steroid hormones, eicosanoids, cholesterol, vitamins, fatty acids and bile acids, many of which affect cardiovascular homeostasis. Experimental studies have demonstrated that several P450s modulate important steps in the pathogenesis of ischemic heart disease (IHD). Areas covered: This article discusses the current knowledge on i) the expression of P450s in cardiovascular and renal tissues; ii) the role of P450s in the pathophysiology of IHD, in particular the modulation of blood pressure and cardiac hypertrophy, coronary arterial tone, ischemia–reperfusion injury and the metabolism of cardiovascular drugs; iii) the available evidence from observational studies on the association between P450 gene polymorphisms and risk of myocardial infarction (MI); and iv) suggestions for further research in this area. Expert opinion: P450s exert important modulatory effects in experimental models of IHD and MI. However, observational studies have provided conflicting results on the association between P450 genetic polymorphisms and MI. Further, adequately powered studies are required to ascertain the biological and clinical impact of P450s on clinical IHD end-points, that is, fatal and nonfatal MI, revascularization and long-term outcomes post MI. Pharmacogenetic substudies of recently completed cardiovascular clinical trials might represent an alternative strategy in this context.